Mechanical Signal Transduction: A Key Role of Fluid Shear Forces in the Development of Osteoarthritis - Li H; Wang W; Wang J (Dove Medical Press, 2024)
Haitao Li, Wei Wang, Jian Wang Department of Orthopedics, Affiliated Hospital of Guizhou Medical University, Guiyang, 55000, People's Republic of ChinaCorrespondence: Jian Wang, Email docwj11@163.comAbstract: Globally, osteoarthritis is a common and highly disabling disease that places a heavy burden on society and medical systems. The role of biomechanical factors in the development of osteoarthritis has gradually received more attention. As a key biomechanical stimulus, fluid shear force is becoming the focus of research for its dual role in maintaining cartilage health and disease progression. This paper conducts an in-depth discussion on the mechanism of fluid shear force in osteoarthritis and its impact on the disease process, aiming to reveal how fluid shear stress affects the development of osteoarthritis by regulating the physiological function and signal transduction pathways of chondrocytes.Keywords: fluid shear, osteoarthritis, chondrocytes, signal transduction, biomechanics